Efeito do Sexo e Idade Sobre o Tempo de Residência de um Quelônio Urbano - JULIA VASCONCELOS ROSSIN ANDRADE DO NASCIMENTO (2021)
Residence time helps characterize animal movement, once it is related with the costs and benefits of staying in a certain place. Since sex and age influence movement patterns of animals, these variables can be important intrinsic factors associated with the residence time. Due to sexual differences on habitat use, freshwater turtles are good models to study the effect of sex and age on residence time. Among turtles, Phrynops geoffroanus is a good study organism due to its abundance in urban areas. This study aimed to understand the movement dynamics and persistence of P. geoffroanus in an urban area, assessing the residence time of males and females of different ages. We conducted the study in the Cabaça stream (RPPN, UFMS), using capture-mark-recapture methods, together with direct visualization of captures and marked animals. We used a Generalized Linear Model for analysis, with the time of residence as response variable and sex, age and body mass as independent variables. There was a negative effect of mass on residence time, and an interactin of sex and age. Thus, young turtles were resident, independently of sex, strategy to maximize survival in an habitat that is rich in resources. Adults showed different residence times, with females having longer times than males. This is explained by sexual behaviour related to different reproductive strategies, with adult males searching for females and females searching for suitable places for reproduction. This way, the understanding of how intrinsic variables influence animal movement and their interactions allowed us to provide more detailed explanations about the behaviour of these organisms.